Pendayagunaan Zakat dan Wakaf untuk Mencapai Maqashid Al-Syari’ah - Amir Sahidin (Badan Wakaf Indonesia, 2021)
Zakat is a property right that must be fulfilled by every Muslim who owns property and has fulfilled the conditions. While waqf is the main means in distributing assets or wealth of the people, as well as a substitute for public facilities. Both are Islamic Shari'a that exist for a noble purpose, bringing benefits both in the world and in the hereafter (maqashid al-syari'ah). Therefore, the study of zakat and waqf will be more important if studied with the maqashid al-syari'ah approach. This article discusses the utilization of zakat and waqf to achieve maqashid al-syari'ah. Through a library research study with a descriptive-analytical approach, it can be concluded that the utilization of zakat to achieve maqashid al-syari'ah includes three maqashid, namely: maqashid dini, maqashid ijtima'i, and maqashid iqtishadi. Meanwhile, the utilization of waqf to achieve maqashid al-syari'ah includes general and specific purposes for which wakat is prescribed. Then all should be directed to achieve al-maqashid al-khamsah, in the form of guarding religion, soul, mind, lineage and property. Keywords: zakat, waqf, maqashid al-syari'ah, maqashid al-khamsah.